2019
DOI: 10.1016/s1473-3099(18)30614-5
|View full text |Cite
|
Sign up to set email alerts
|

Cadazolid for the treatment of Clostridium difficile infection: results of two double-blind, placebo-controlled, non-inferiority, randomised phase 3 trials

Abstract: This is a repository copy of Cadazolid for the treatment of Clostridium difficile infection: results of two double-blind, placebo-controlled, non-inferiority, randomised phase 3 trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 25 publications
1
33
0
3
Order By: Relevance
“…In pre-clinical studies, cadazolid showed a potent bactericidal in vitro activity against CD (MIC90 of 0.25 mg/L) and a low propensity for resistance development [174][175][176]. The results for the IMPACT I and IMPACT II phase 3, randomized clinical trials were recently published [177]. While safe and well tolerated, cadazolid failed to achieve the primary end-point of non-inferiority vs. vancomycin for clinical cure [177].…”
Section: Question 9 When and How To Report Clinicians The Results Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In pre-clinical studies, cadazolid showed a potent bactericidal in vitro activity against CD (MIC90 of 0.25 mg/L) and a low propensity for resistance development [174][175][176]. The results for the IMPACT I and IMPACT II phase 3, randomized clinical trials were recently published [177]. While safe and well tolerated, cadazolid failed to achieve the primary end-point of non-inferiority vs. vancomycin for clinical cure [177].…”
Section: Question 9 When and How To Report Clinicians The Results Ofmentioning
confidence: 99%
“…The results for the IMPACT I and IMPACT II phase 3, randomized clinical trials were recently published [177]. While safe and well tolerated, cadazolid failed to achieve the primary end-point of non-inferiority vs. vancomycin for clinical cure [177]. As a result, to the best of our knowledge, efforts to commercialize cadazolid for CDI have been halted.…”
Section: Question 9 When and How To Report Clinicians The Results Ofmentioning
confidence: 99%
“…A similar decision was observed with cadazolid, which met the primary endpoint in the phase 2 study, but failed to meet the endpoint in the phase 3 trials (IMPACT I and II, NCT01987895 and NCT01983683). 89…”
Section: Discussionmentioning
confidence: 99%
“…According to the currently postulated pathophysiology, the infectious process occurs following a disturbance to the gut’s normal microbiota, leading to an overgrowth of Clostridioides difficile . While symptoms can range from mild to severe, its complications of toxic mega-colon and shock contribute to high morbidity and mortality rates [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cadazolid is a highly acidic novel fluoroquinolone-oxazolidinone antibiotic with strong lipophilic properties [ 2 , 4 ]. This organic heterocyclic compound’s quinolone characteristics allow it to act as a potent inhibitor of both DNA and protein synthesis.…”
Section: Introductionmentioning
confidence: 99%